PRACTICES FOR PREVENTION NEEDLESTICK AND SHARPS INJURIES AMONG NURSING STUDENTS - Anh Tran Thi Quynh; Katrina Einhellig (Belitung Raya Foundation, Indonesia, 2017)
Background: Needlestick and sharp injuries are a serious hazard in any health care setting for health care workers and students during clinical practice. Thus, the efforts to prevent the needlestick and sharps injuries are needed and considered a part of the routine practice.Objective: This study aimed to investigate the frequency of nursing students in doing the correct practice in prevention needlestick and sharps injuries.Methods: This cross- sectional study was conducted between 2013 and 2014 in nursing students of Tien Giang Medical College who participated in clinical practice. There were 360 students participated in the study using simple random sampling. Data were collected using the practical assessment checklist and demographic characteristics questionnaire. Data were processed using STATA 12.0, and analyzed using Chi-square and Fisher test.Results: The students who did general practice correctly accounted for 52.50%, and those who did practice incorrectly was 47.5%. The students who used gauze or wool wrap in inhaler were 59.7%, wearing gloves in practice (39.2%), do not disassemble needles from syringes after injection 50%, and removing needles into barrel after injection (65.6%). There was statistically significant relationship between time of participation in clinical practice and correct practice with p-value 0.04 (<0.05)Conclusion: The correct practice of nursing students related to the prevention of needlestick and sharps injuries remains low. There was a significant relationship between time of participation in clinical practice and correct nursing practice. It is suggested that students must be taught about the risk of infection at the beginning of clinical practice, and constantly reminded throughout the learning process, especially for injection safety awareness, knowledge and techniques about the risk of transmission of HBV, HCV and HIV by sharp objects in the healthcare facility.